Adult presentation of Shwachman-Diamond syndrome complicated by liver cirrhosis and pancreatic fat infiltration: A case report - Guo, Hai-Jun (World journal of hepatology, 2025)
BACKGROUND Shwachman-Diamond syndrome (SDS) is a rare genetic disorder that affects multiple organs, primarily the liver. Most patients are diagnosed during infancy or early childhood. As they grow older, the majority of affected children may experience spontaneous remission, and cases of cirrhosis in adults are rarely reported. CASE SUMMARY A 36-year-old male patient presented with massive ascites. Laboratory tests revealed pancytopenia and a serum-ascites albumin gradient greater than 1.1 g/dL. An abdominal computed tomography scan demonstrated cirrhosis, splenomegaly, pancreatic fat infiltration, and a substantial accumulation of peritoneal fluid. Gastroscopy identified esophageal varices. Liver stiffness measurement indicated a value of 32.7 kPa. Based on the results of auxiliary examinations, common causes of cirrhosis were excluded, and a mutation in the Shwachman-Bodian-Diamond syndrome gene was ultimately identified through whole-exome sequencing. The patient was diagnosed with cirrhosis secondary to SDS. Following the correction of hypoalbuminemia and administration of diuretics, the patient's ascites resolved. CONCLUSION Patients with liver cirrhosis who also exhibit pancreatic fat infiltration and pancytopenia necessitate further exon testing to exclude the possibility of SDS.